Keagenan Perempuan pada Krisis Iklim: Dekolonisasi Metode Feminis - Titiek Kartika Hendrastiti; Rahmanta Setiahadi (Jurnal Perempuan, 2022)
This article aims to discuss the relationship between the promotion of women’s agency and vulnerable groups with the changing trends in the orientation of social research methods towards decolonization in the strands of the feminist approach. All the world communities, especially the marginal groups who have intersectional vulnerabilities, are starting to redefine their experiences in this climate crisis. It is proven that their concrete resilience is genuine, innovative, creative, and able to preserve their lives in a sustainable manner. Our attention should be deeper towards their simple efforts to free themselves from the “oppression of global powers”. This research was conducted in two villages of the Exclusive Economic Zone (KEE) Banyuwangi, East Java, called Wringinputih and Kedunggebang. The framework used is postcolonial feminist and applies a feminist political ecology (FPE) method. Fieldwork adopts focus group discussion, field talk, and participatory observation. The doubts of marginal communities about their agency in the climate crisis is a challenge for postcolonial feminist researchers. In fact, by using a feminist postcolonial approach, the practices of forest landscape governance (FLG) clearly record the involvement of women and marginalized groups. Here it is the novelty of the article, a decolonization method in FLG